ANALISIS WORK LIFE BALANCE, BUDAYA ORGANISASI DAN KEPUASAN KERJA TERHADAP PRODUKTIVITAS KARYAWAN DI PT. PANCA DEWATA SINGARAJA-BALI - Sandhi Putra Nurhadi, Wayan; Ni Putu Nina Eka Lestar; I Wayan Sunia (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2024)
Employee work productivity is the result of work in terms of quality and quantity achieved by employees in carrying out their duties in accordance with the responsibilities given to them. Based on the criteria, the researcher can determine a sample size of 35% of the existing population of 132 respondents, so that the research sample totals 46 respondents (rounded). Purposive sampling technique. Types of Quantitative Data and Qualitative Data sourced from Primary Data Sources and Secondary Data collected through Documentation and Questionnaires. The data analysis technique uses smart PLS SEM (Partial Least Square - Structural Equation Modeling) software. The research results show that the influence of work life balance variables on employee work productivity is positive and significant. The influence of work life balance variables on job satisfaction is positive and significant. The influence of organizational culture variables on employee work productivity is positive and significant. The influence of organizational culture variables on job satisfaction is positive and not significant. The influence of the job satisfaction variable on employee work productivity is positive and significant. The influence of work life balance on employee work productivity through positive and significant job satisfaction. The influence of organizational culture on employee work productivity through positive and insignificant job satisfaction.